Acting liturgically: Wolterstorff’s philosophical reflections on religious practice - Havenga, Marnus (Stellenbosch Theological Journal, 2021)
This review article offers an engagement with Nicholas Wolterstorff's recent publication, Acting liturgically: Philosophical reflections on religious practice. It begins by contextualising the project, tracing Wolterstorff's lifelong interest in liturgy, as documented in his memoir, In this world of wonders. This is followed by a careful exposition of each of the book's four sections (with the headings "Liturgy, Enactments and Scripts, - Liturgy and Scripture, - God in the Liturgy" and "Liturgy, Love and Justice"). The article concludes with a few critical observations about the book in which it is shown why this is indeed a significant text which makes an important contribution to the (philosophical) study of liturgy.